Perkembangan Kebijakan Pendidikan di Indonesia: A Systematic Leterature Review - Daud, Yusri M (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Curriculum policies in Indonesia have undergone changes since the pre-independence period until now. This study aims to analyze policy developments in Indonesia so that it can provide an overview of the mapping of the themes that have been researched, the mapping methodology used in the article, and the year of publication of the article. The method used in this study is Systematic Literature Review (SLR) by using the keyword education policy in Indonesia on the Google Scholar engine using Indonesian, the articles searched are limited to 2016 to 2024. The method used in this study is Systematic Literature Review (SLR) by using the keyword education policy in Indonesia on the Google Scholar engine using Indonesian, the articles searched are limited to 2016 to 2024. Thus, it can be concluded that education policy in Indonesia has experienced significant development and has an impact on learning.